Isolation, Biosynthesis, and Biological Activity of Polycyclic Xanthones From Actinomycetes - Yu, Hui-Qing; Li, Gang; Lou, Hong-Xiang (Frontiers in Microbiology, 2022)
Natural products from actinomycetes serve as a crucial source of clinical pharmaceuticals, especially antibiotics and anticancer agents. Among them, polycyclic xanthones belong to a growing group of highly oxygenated aromatic polyketides with a xanthone-containing angular hexacyclic framework. These biosynthetically unique small molecules are of great interest due to their wide spectrum of biological activities, especially the remarkable antibacterial activity against Gram-positive bacteria and the significant antineoplastic effects towards various cancer cells at nanomolar concentrations. Their complex structures and significant bioactivities have aroused considerable attention in the chemical and biological communities in recent decades. This review covers the isolation, the biosynthesis, and the biological studies towards these structurally complex and biologically active molecules.